Association of social factors with low birth weight: a narrative review - Marimuthu, Yamini; Sarkar, Sonali; Sakthivel, Manikandanesan; K., Yuvaraj; N., Bharathnag; Sarveswaran, Gokul (International Journal Of Community Medicine And Public Health, 2018)
Low birth weight (LBW) is a major cause for neonatal morbidity and mortality. Apart from various medical risk factors, social factors also have an impact on birth weight. The objective of the study were to review the globally available evidences on the association between LBW and social factors like social support, spouse support and spouse abuse experienced by the mothers during the antenatal period. A narrative review was done during 2017 in which various literatures available “PubMed” and “Google Scholar” related to the social factors like social support, spouse support and spouse abuse and low birth weight were reviewed after checking for full text availability and removing duplicates. The antenatal mothers with high perceived social support was associated with 60% lesser odds of having LBW. Mothers with high perceived spouse support had 23% lesser odds of having LBW both of which might act through financial, moral, emotional and behavioral pathways. Various studies have found positive association between LBW and spouse abuse and the OR ranged from 1.3 to 3.8. The definitions and instruments used for the social support, spouse support and spouse abuse are varied making it difficult to interpret varied results in different study settings. With the available few evidences it can be concluded that lack of spouse support and social support and the presence of spousal abuse during antenatal period increases the odds of still birth, preterm birth and low birth weight among children.